2014
DOI: 10.17219/acem/37330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Bacillus Calmette-Guerin Substrains on Growth Inhibition of T24 Bladder Cancer Cells and Cytokines Secretion by BCG Activated Peripheral Blood Mononuclear Cells of PBMCs

Abstract: Background. Bladder carcinoma is the most common malignancy of the urinary tract. Approximately 75-85% of patients present non-muscle invasive bladder cancer (NMIBC). Standard primary treatment for NIMBC is transurethral resection (TUR) followed by intravesical Bacillus Calmette-Guerin (BCG) immunotherapy. BCG has been accepted as the most effective agent in clinical use against NMIBC. Various BCG substrains are used worldwide for bladder cancer immunotherapy although the impact of used BCG substrain on BCG an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The mechanism in which BCG vaccine ameliorates effectively cancer was not well-explored. Several studies investigated the alteration of different types of cytokines by BCG vaccine 59 62 , such as Th1’s cytokines (IFN-γ, TNF-α, IL-12) and Th2’s cytokines (IL-10, IL-4). These substances play roles in regulation of natural killer cells, macrophages or cytotoxic T lymphocytes cells 61 , which have antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism in which BCG vaccine ameliorates effectively cancer was not well-explored. Several studies investigated the alteration of different types of cytokines by BCG vaccine 59 62 , such as Th1’s cytokines (IFN-γ, TNF-α, IL-12) and Th2’s cytokines (IL-10, IL-4). These substances play roles in regulation of natural killer cells, macrophages or cytotoxic T lymphocytes cells 61 , which have antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: PBL, peripheral blood leukocyte; BCG, bacillus Calmette-Guerin; MST, median recurrence-free survival time. secreted from activated PBLs, 30 could also predict BCG therapy effectiveness. We therefore conducted the analysis in 112 urine samples from NMIBC patients receiving BCG therapy.…”
Section: The Association Between High Urinary Il-8 Level and Tumor Rementioning
confidence: 99%
“…While in-vitro testing, the BCG sub-strains i.e. Moreau, Tice and RIVM, have also shown inhibitory effect on human bladder cancer cell line, T24, which has been attributed to presence of cytotoxic mycolic acids on cell surface of these strains [83]. Moreover, presence of Th1 cytokines such as TNF-α and IFN-γ enhance tumor cell proliferation by inhibiting activity of BCG strains.…”
Section: Intravesical Immunotherapy With Bcgmentioning
confidence: 99%
“…In a systemic meta-analysis, it was concluded that compared to BCG alone, the synergistic effect of intravesical BCG and chemotherapy improved recurrence free survival, overall survival and disease specific survival with significantly decreased rate of fever, irritative symptoms and hematuria therapy among NMIBC patients [93]. Nonetheless, the therapeutic efficacy of BCG is undermined owing to its associated local and systemic side effects such as dysuria, haematuria, cystitis, sepsis, malaise and fever [83,90]. Moreover, in case of observed severe side effect such as sepsis, the BCG therapy is withdrawn and followed by tuberculosis treatment [94].…”
Section: Intravesical Immunotherapy With Bcgmentioning
confidence: 99%